Tradeoff between Stem Hydraulic Efficiency and Mechanical Strength Affects Leaf–Stem Allometry in 28 Ficus Tree Species - Fan, Ze-Xin; Sterck, Frank; Zhang, Shi-Bao; Fu, Pei-Li; Hao, Guang-You (Frontiers in Plant Science, 2017)
Leaf-stem allometry is an important spectrum that linked to biomass allocation and life history strategy in plants, although the determinants and evolutionary significance of leaf-stem allometry remain poorly understood. Leaf and stem architectures – including stem area/mass, petiole area/mass, lamina area/mass, leaf number, specific leaf area and mass-based leafing intensity – were measured on the current-year branches for 28 Ficus species growing in a common garden in SW China. The leaf anatomical traits, stem wood density, stem anatomical and mechanical properties of these species were also measured. We analyzed leaf-stem allometric relationships and their associations with stem hydraulic ad mechanical properties using species-level data and phylogenetically independent contrasts. We found isometric relationship between leaf lamina area/mass and stem area/mass, suggesting that the biomass allocation to leaf was independent to stem size. However, allometric relationship between leaf area/mass and petiole mass was found, indicating large leaves invest a higher fractional of biomass in petiole than small ones. Leafing intensity, i.e. leaf numbers per unit of stem mass, was negatively related with leaf and stem size. Species with larger terminal branches tend to have larger vessels and theoretical hydraulic conductivity, but lower wood density and mechanical strength. The size of leaf lamina, petiole and stem were correlated positively with stem theoretical hydraulic conductivity, but negatively with stem wood density and mechanical strength. Our results suggest that leaf-stem allometry in Ficus species was shaped by the trade-off between stem hydraulic efficiency and mechanical stability, supporting a functional interpretation of the relationship between leaf and stem dimensions.